Noninvasive and Continuous Monitoring of Systolic and Diastolic Blood Pressure in Finger Arteries during and after the Acupuncture of the Carotid Sinus - SHIMAZU, Hideaki; ITO, Hiroshi; KINOSHITA, Haruto; AKIMOTO, Megumi (Zen Nihon Shinkyu Gakkai zasshi (Journal of the Japan Society of Acupuncture and Moxibustion), 1987)
By means of indirect sphygmomanometer called “volume compensation technique” systolic and diastolic blood pressure in finger arteries were noninvasively and continuously measured during and after the “doshi” which is the acupuncture of the carotid sinus. After 15-min resting, 2-min puncture of the right and left carotid sinus was carried out in 23 healthy subjects (8 males and 15 females, aged 18-55). Finger arterial blood pressure was measured during the rest and the in-situ puncture, and then at 30 minutes after the withdrawing. For the control the dodged puncture of the carotid sinus was also made in other 6 healthy subjects (2 males and 4 females, aged 23-55). Decreasing in blood pressure were observed during and after the doshi in 87% of the subjects. The mean magnitude of the decrease in the systolic and diastolic pressure at 15-21 minutes after the withdrawal of the needle were 12 and 10mmHg, respectively. Pulse pressure and heart rate showed little changes during the experiment. To the control dodged puncture, the maximum change in the systolic and diastolic pressure were 3.4 and 5.0mmHg, respectively, which were within the range of the physiological blood pressure variation. These data suggests that the blood pressure response to the “doshi” may not be induced by the vagal cardiac inhibition but by the change in peripheral vascular resistance.